2015
DOI: 10.3348/kjr.2015.16.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Propensity Score Matching: A Conceptual Review for Radiology Researchers

Abstract: The propensity score is defined as the probability of each individual study subject being assigned to a group of interest for comparison purposes. Propensity score adjustment is a method of ensuring an even distribution of confounders between groups, thereby increasing between group comparability. Propensity score analysis is therefore an increasingly applied statistical method in observational studies. The purpose of this article was to provide a step-by-step nonmathematical conceptual guide to propensity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
120
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 47 publications
0
120
0
2
Order By: Relevance
“…It is a statistical tool to create a balanced distribution of the analyzed confounders. 32 Therefore, it is important to collect sufficient information on all relevant confounders. 32 Our study showed that the rates of complications, especially of non-surgical complications, were higher in patients receiving chemotherapy before surgical resection of CRLM (Table 1).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is a statistical tool to create a balanced distribution of the analyzed confounders. 32 Therefore, it is important to collect sufficient information on all relevant confounders. 32 Our study showed that the rates of complications, especially of non-surgical complications, were higher in patients receiving chemotherapy before surgical resection of CRLM (Table 1).…”
Section: Discussionmentioning
confidence: 89%
“…However, one has to keep in mind that PSM is not able to completely reduce the heterogeneity of data between two or more groups. It is a statistical tool to create a balanced distribution of the analyzed confounders . Therefore, it is important to collect sufficient information on all relevant confounders …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also used a statistical method, namely propensity score matching analysis, which could control bias effectively and minimize the imbalance among groups in observational studies. 34 Our research also has several limitations. The study was a retrospective, multicenter program, and the data were self-reported by the site investigator, which included selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was compared between women who were managed by intrauterine balloon tamponade and women who underwent uterine artery embolization using a logistic regression model, resulting in estimated odds ratios (OR) with 95% confidence intervals (CI) . Differences in secondary outcome measures were estimated by Mann‐Whitney U testing before propensity score‐matching, and by the Wilcoxon signed‐rank test after propensity score‐matching, where a two‐tailed P value <0.05 was considered statistically significant . To evaluate the robustness of our study findings with regard to propensity score‐matching, a sensitivity analysis was performed of the primary outcome measure by including the propensity score as a covariate in the logistic regression model to compare the primary outcome measure between both intervention groups, under the assumption that the propensity score has a linear functional relation with the log odds of the primary outcome …”
Section: Methodsmentioning
confidence: 99%